Competency-based Medical Education of Biochemistry: The Students’ Feedback - Pradeep K Japa; Munvar Fathima; Sangeeta Samudrala; Padma Yalamati (Indian Journal of Medical Biochemistry)
Aim: To obtain feedback from first year medical undergraduates over biochemistry competency-based medical education (CBME) curriculum. Background: Medical education needs to be amended according to the advances and needs of the students. Competency-based medical education is the most widely practiced medical curriculum worldwide. It provides the framework for teaching and learning using various new methods. However, feedback from students on such strictly practiced curriculum is not available; hence, this study was initiated. Materials and methods: All the 150 students of the 2023–2024 academic batch at Government Medical College, Jagtial, Telangana, were asked for a feedback through Google forms containing 52 questions on the biochemistry curriculum practiced. The responses were analyzed using Microsoft Excel, Statistical Package for the Social Sciences, version 20, and represented as percentages. Results: Out of the 124 students who responded, most agreed (p < 0.05) or favored the new CBME curriculum in terms of knowledge, skill, and clinical application. However, there seems to be a minority of students of opinions that the course offered is more advanced than required [53 (42.7%)], inadequate time for assessments [13 (10.5%)], and ineffectiveness of newer methods of learning [17 (13.7%)]. Data gathered suggest that students have difficulty with metabolic pathways, clinical application, molecular biology, and its techniques in the same order. Discussion: Areas involving rote memory, metabolism, and clinical relevance appear to be critical in medical students’ learning of biochemistry. The new CBME curriculum has changed the course in many ways, increased the ease of learning, and developed curiosity in the students; however, our observations suggest that there is a need for regular feedback from the students and instructors that might help in revising and updating the curriculum.